A comprehensive study of psychological well-being and traditional Chinese medicine constitutions among model workers in Beijing - Cao, Hongli; Chen, Xianyang; Song, Yige; Li, Shawn Xiang; Ma, Hui; Zhang, Guosheng; Gong, Tianyu; Yu, Hong; Liu, Zijin (Frontiers in Psychiatry, 2024)
Background: Body constitution is the foundation of Traditional Chinese Medicine (TCM), and model workers consist of a special group of workers within China. This study aims to research the relationship between the physical body constitutions based on TCM and the mental health of model workers.We recruited 314 model workers from Beijing Rehabilitation Hospital to conduct the questionnaires such as SCL-90 and CCMQ to investigate if there is an association between mental health status and TCM body constitutions. We performed a Partial Least Squares Path Modeling (PLS path modeling).Results: Our path model results revealed associations between different TCM constitution types and SCL scores, which serve as indicators of psychological well-being. Our research findings demonstrate a strong correlation between the Balanced constitution and elevated levels of psychological well-being, with a path coefficient of -0.503. In contrast, the other eight constitutional types exhibit path coefficients exceeding 0.3, indicating a tendency toward lower levels of psychological well-being. We also investigated the intricate connections between various TCM constitutional types and both mild and severe psychological well-being.In conclusion, the Balanced constitution continues to be closely associated with higher levels of psychological well-being, while the remaining eight body constitution types are consistently linked to lower levels of psychological well-being.